Instrument for Assessing Respiratory Disorders in Children: A Systematic Review - Lhesmi Tri Yana Putri S; Mega Hasanul Huda; Astuti Astuti; Alfin Nugroho; Dessie Wanda (Indonesian Journal of Global Health Research, 2026)
Respiratory disorders remain the most common cause of morbidity and mortality in children under 5 years of age worldwide. Pneumonia and asthma are part of this. To reduce pediatric mortality, valid and reliable instruments are needed to guide the further treatment process appropriately. This systematic review aimed to identify the sensitivity and specificity of the Respiratory Index of Severity in Children (RISC) and Test for Respiratory and Asthma Control in Kids (TRACK) instruments in children with pneumonia and asthma. The study was conducted by searching articles from the online databases PubMed, Scopus, JSTOR, ProQuest, Science Direct, and EBSCOhost from 2015 to 2025. Two reviewers independently assessed the study quality using QUADAS-2. Of the 969 articles found, 6 articles were selected for  analysis. The RISC instrument obtained various sensitivity values with a cut-off ≥3, namely 21.3% to 94.1% and specificity values of 73.6% to 89.51%. In the TRACK instrument, the sensitivity values ranged from 75.6% to 81.4% and the specificity values ranged from 70.9% to 80.0% using a cut-off of 80. Both instruments can be used to assess the severity and mortality risk of childhood pneumonia and the assessment of asthma symptoms and control in children.